2013
DOI: 10.1371/journal.pcbi.1003058
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Energy Landscape of Activation Gating of the Bacterial Potassium Channel KcsA

Abstract: The bacterial potassium channel KcsA, which has been crystallized in several conformations, offers an ideal model to investigate activation gating of ion channels. In this study, essential dynamics simulations are applied to obtain insights into the transition pathways and the energy profile of KcsA pore gating. In agreement with previous hypotheses, our simulations reveal a two phasic activation gating process. In the first phase, local structural rearrangements in TM2 are observed leading to an intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 64 publications
4
23
0
Order By: Relevance
“…Initial tests using the adenosine A 2A receptor and β 2 adrenergic receptor suggested that this method could reliably predict the orientation of the active TM6 position based on an inactive starting structure (data not shown). The best scoring active and inactive models were used as starting conformations for essential dynamics simulation [33] . Each protein was embedded in an equilibrated solvated membrane consisting of 280 POPC lipids.…”
Section: Methodsmentioning
confidence: 99%
“…Initial tests using the adenosine A 2A receptor and β 2 adrenergic receptor suggested that this method could reliably predict the orientation of the active TM6 position based on an inactive starting structure (data not shown). The best scoring active and inactive models were used as starting conformations for essential dynamics simulation [33] . Each protein was embedded in an equilibrated solvated membrane consisting of 280 POPC lipids.…”
Section: Methodsmentioning
confidence: 99%
“…It is conceivable that an energetic barrier needs to be overcome in WT for channel opening as shown in a previous simulation study on KcsA. 41 …”
Section: Discussionmentioning
confidence: 92%
“…Potential of mean force (PMF) calculations were performed as described previously. 41 Briefly, the main conformational changes in the most prominent G143E d opening simulation were obtained by principal component analysis. The first eigenvector obtained by this PCA was used as a reaction coordinate.…”
Section: Methodsmentioning
confidence: 99%
“…Potassium channels typically contain a selectivity filter, which selects for 4 potassium over other ambient ions with high affinity, as well as an activation 'gate' that 5 opens the channel and initiates the flow of potassium. In many potassium channels, 6 however, the channel spontaneously stops conduction even when potassium ions and hypothesized that the site of inactivation is in the selectivity filter, where potassium 18 ions are bound and conducted through the membrane [2,9,23,40]. This mechanism is 19 termed activation-coupled inactivation, i.e., and proposes that an allosteric coupling 20 between the selectivity filter and activation gate (like the pH gate in KcsA) lead to a 21 decrease in potassium affinity at the selectivity filter after activation.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is 19 termed activation-coupled inactivation, i.e., and proposes that an allosteric coupling 20 between the selectivity filter and activation gate (like the pH gate in KcsA) lead to a 21 decrease in potassium affinity at the selectivity filter after activation. A direct 22 measurement of the potassium ion affinity at the selectivity filter by solid state nuclear 23 magnetic resonance (SSNMR) was carried out on KcsA embedded in an authentic lipid 24 environment [42]. The potassium ion affinity changed from K apparent = 14 ± 1 mM at 25 pH 3.5 to 4 ± 1 µM at pH 7.5.…”
Section: Introductionmentioning
confidence: 99%